2022
DOI: 10.46481/jnsps.2022.355
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Time on the Syntheses of Carbon Nanotubes via Domestic Oven

Abstract: In this study, carbon nanotubes (CNTs) were synthesized directly on coated silicon substrate via commercial microwave oven at 2.45 GHzf for3 minutes (Sample A) and 4 minutes (Sample B). The plasma provides the required temperature for catalytic decomposition of carbon source (polyethylene) at 750 ?C under atmospheric pressure. Raman spectroscopy, Field Emission Scanning Electron Microscopy (FESEM), High Resolution Transmission Electron Microscope (HRTEM), X-ray diffractometer (XRD) techniques are used to chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The structure of graphene oxide produced by the different electrolytes is investigated using Raman spectroscopy, achieved by the adoption of a uniform excitation laser of 514.5 nm across all the samples. Raman spectroscopy is a non-destructive vibrational technique that is almost indispensable in the study of macro, micro, or nano carbon materials because it reveals the bonding, defects, and geometric structure [38,39]. The Raman spectra of graphene oxide show characteristic principal bands denoted as 2D, G, and D bands with significant differences in their relative intensities and shape profiles (see Figure 1).…”
Section: Structure and Defect Concentration Of The Graphene Oxides Pr...mentioning
confidence: 99%
“…The structure of graphene oxide produced by the different electrolytes is investigated using Raman spectroscopy, achieved by the adoption of a uniform excitation laser of 514.5 nm across all the samples. Raman spectroscopy is a non-destructive vibrational technique that is almost indispensable in the study of macro, micro, or nano carbon materials because it reveals the bonding, defects, and geometric structure [38,39]. The Raman spectra of graphene oxide show characteristic principal bands denoted as 2D, G, and D bands with significant differences in their relative intensities and shape profiles (see Figure 1).…”
Section: Structure and Defect Concentration Of The Graphene Oxides Pr...mentioning
confidence: 99%
“…The results of the study showed that the calculated carbon quality was equal to 1.01 and 1.02 for sample A and sample B, respectively; with an average diameter from 6.0 to 10.0 nm. A high‐intensity ratio was associated with a defective mode in MWCNTs 34 …”
Section: Introductionmentioning
confidence: 99%
“…A highintensity ratio was associated with a defective mode in MWCNTs. 34 Keeping the above facts into consideration, the main objectives of the work are summarized below:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation